Hubungan Pengetahuan dan Sikap Perawat dengan Penerapan Patient Safety pada Masa Pandemi Covid-19 di Ruang IGD RSUD X - Yusril Sindring; Heriyana Amir; Sitti Rahma Soleman; Hairil Akbar (Lentera : Jurnal Ilmiah Kesehatan dan Keperawatan, 2021)
Patient safety is a system that aims to provide care for patients safely as an effort to prevent unwanted events. Written reports of patient safety incidents that occur in Indonesia are categorized by the number of cases based on the result of the incident, KNC 38%, KTC 31% and KTD 31%. The purpose of the study was the relationship between knowledge and attitudes of nurses with the application of patient safety during the COVID-19 pandemic in the emergency room of RSUD X. This type of research used an analytical observational study with a cross sectional approach. The population in this study were all 39 nurses in the emergency room and a total sample of 39 nurses using a total sampling technique. Data analysis using Chi square test. The results of the analysis obtained knowledge (p = 0.007) and attitudes (p = 0.022) related to the application of patient safety during the Covid-19 pandemic in the ER Room of RSUD X. From the explanation above, it is expected that all nurses should implement patient safety when examining patients.